Collect and preserve (Wiesbaden)
x, 230 sayfa, [10] sayfa resim (renkli)
Keywords: “The use of writing for the preservation and transmission of administrative, scientific, literary and sacred knowledge has a long history. From the third millennium BCE on, many forms of social processes - intellectual, religious, political and others - have been increasingly materialized in the form of a variety of document types (tablets, bones, papyri, scrolls, parchments, books). Some of them were collected in archives or libraries that were dependent on royal palaces, governmental institutions and temples but also in private contexts. The publication 'Collect and Preserve' assembles a number of studies devoted to material aspects of collecting texts in ancient Egypt, Mesopotamia, Medieval Japan, and Korea” –